Colorimetric and fluorescent probes for real-time naked eye sensing of copper ion in solution and on paper substrate - Dugang Chen (Royal Society Open Science, 2017)
In this paper, BT ((E)-2-(4-(4-(bis(pyridin-2-ylmethyl)amino)styryl)-3-cyano-5,5-dimethylfuran-2(5H)-ylidene)malononitrile) with strong donor–π-acceptor structure was synthesized, which showed both colorimetric and fluorescent sensing ability toward Cu2+ with high selectivity and sensitivity. Job plot and mass spectra measurement revealed a 1 : 1 coordination mode between Cu2+ and probe BT in ethanol/HEPES (1 : 4 v/v) buffer (pH 7.2) solution, and the binding constant was calculated to be 3.6 × 104 M–1. The colour of BT solution (10 µM) immediately turned from purple red to yellow and the red fluorescence was quenched obviously when a certain amount of Cu2+ was added, which enabled a dual-channel detection of Cu2+. A paper strip pre-stained with BT solution was further fabricated and it also showed excellent sensing ability toward Cu2+ with a detection limit as low as 10−6 M with the naked eye, which represents better portability and operation simplicity that is favourable for on-site analysis of Cu2+ in water.